ANALISIS CAMPUR KODE DALAM VIDEO TIKTOK HALLOSAER - Sarifatul Jannah; Sinta Salesetiawati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the use of code-mixing in HallosaEr's TikTok videos, a TikToker from Madura who combines Madurese and Indonesian languages in his content. Using a qualitative research method with a descriptive analysis approach, the study reveals that HallosaEr employs code-mixing effectively and creatively in his TikTok videos. The use of code-mixing is not merely a random switch, but a planned and effective communication strategy to build familiarity with the audience, highlight Madurese cultural identity, adjust to conversation contexts, and enhance content appeal. Factors influencing code-mixing include Madurese cultural identity, desire for audience familiarity, social media trends, need to reach a broader audience, and adaptability to conversation contexts. This study demonstrates that HallosaEr's use of code-mixing on TikTok is an effective and creative communication strategy for building connections with the audience and creating engaging and memorable content.